Digital Transformation in Higher Education: Education as a Service - Zahedi, Mohammad Hadi (AI and Tech in Behavioral and Social Sciences, 2024)
Today, education plays a significant role in the economic, social, cultural, and even political growth of every country. As learning is more influenced by modern technologies than ever before, learning and teaching are continuously evolving. Topics such as the Internet of Things, virtual reality, augmented reality, the metaverse, digital twins, generative artificial intelligence, and cloud computing are transforming individual and interactive learning methods. Effective teaching standards provide learners with high-quality and interactive training, such as e-learning courses specifically designed for students and based on smart technology. Nowadays, e-learning and smart learning have become highly popular trends in educational technology. Interactive and smart education is an engaging style that provides digital content and an education-focused environment for both teachers and learners using digital age technologies. The emergence of new concepts in the era of the digital revolution, such as platform universities, has opened up new research fields for scholars in the domains of education and educational technology. This article aims to demonstrate how leveraging modern technologies in the learning domain can foster a shift in approaches and perspectives toward digital higher education as a service provider to its applicants. Thus, this article discusses the concept of "Education as a Service" in smart and interactive learning and examines various aspects of "Education as a Service" through a multi-layer cloud model, addressing the opportunities and challenges of this type of education.